Model Perilaku Penggunaan Aplikasi BSI Mobile Pada Nasabah PT. Bank Syariah Indonesia, Tbk. KCP Banjarmasin Sentral Antarari - Rizqa Putrianaridha Sedar; Irwansyah (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2026)
This research aims to examine the behavior of BSI KCP Banjarmasin Sentra Antasari customers in using mobile banking using the Technology Acceptance Model (TAM). The TAM model consists of the variables perceived ease, perceived usefulness, attitude to use, interest in use, and using. The study employs a quantitative research method with an explanatory type and utilizes SmartPLS data analysis. Data is collected through the distribution of questionnaires to BSI customers at KCP Banjarmasin Sentra Antasari who use the BSI Mobile application. The results of this test prove that perceived ease of use has a positive effect on attitudes towards using mobile banking, perceived usefulness has a positive effect on attitudes towards using mobile banking, attitudes towards use have a positive effect on behavioral interest in using mobile banking, and behavioral interest has a positive effect on using mobile banking